Assessing Environmental Impact of Earthquake-Induced Damage for an Italian Case-study Building - Galasso, Carmine; ICASP14; Aljawhari, Karim; Gentile, Roberto (My University, 2023)
This study assesses environmental impacts due to the repair of earthquake-induced damage considering an old reinforced concrete (RC) frame representative of those built in Italy before the 1970s. Such impacts, expressed in terms of embodied carbon, represent a considerable component of buildingsﾒ life-cycle embodied carbon in seismically-prone regions. Embodied carbon is the term for greenhouse gas emissions associated with manufacturing and using a product/service. In the case of materials for building repairs, this includes extraction, manufacturing, transporting, construction, maintenance, and disposal. The seismic damage sustained by the case-study frame is first evaluated using the FEMA P-58 methodology. Specifically, the frameﾒs nonlinear response is analysed against increasing ground-shaking intensities, followed by estimating the damage incurred by its individual components via ad-hoc fragility models. Damage is then converted to embodied carbon by calibrating consequence models specifically developed for Italian structural and non-structural building components. This is accomplished by: 1) collecting environmental-impact data from Italian manufacturers of relevant construction materials and; 2) defining suitable structure-specific damage levels and the required repair work for every component. Results show that the embodied carbon induced by seismic damage throughout the case-study buildingﾒs life cycle might exceed 25% of that generated during its initial construction (pre-use phase).
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED